Power up : taking charge of your financial destiny - Dvorikin, Howard S. (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
A proven survival guide for these economically rocky, debt-ridden times Millions of people suffer financial hardship due to job loss and a variety of other factors. What you need to do in order to take control of your financial destiny includes changing the way you confront and deal with everyday pressures related to shopping, advertising, credit cards, keeping up with the Joneses, and spending money. In Power Up, Howard Dvorkin'founder of Consolidated Credit Counselling Services draws on his years of experience helping thousands of people overcome devastating financial hardship. He provides you with time-tested strategies and powerful tools to rebuild your financial life on a solid and enduring foundation. Besides discussing guidelines for creating a realistic budget and sticking to it, Dvorkin also shares tips on how to learn to live without credit cards and love doing it as well as puts you in a better position to understand the difference between what you want and what you need.-Filled with effective budgeting tools, worksheets, and other valuable forms -Provides a look at the tricks that lenders and credit card companies use to make you a slave to debt -Offers ideas on how to redirect your urge to shop into activities that satisfy your deeper needs and methods to improve your fiscal psychology -Contains priceless advice on how to educate your kids about money and personal finance Do you want a chance to start over again with a clean slate' Do you want the peace of mind that comes with knowing you're in charge of your financial destiny' If you answered yes to any of these questions, then it's time to Power Up!
Power Up: Taking Charge of Your Financial Destiny -- Copyright -- Contents -- Introduction -- Chapter 1: The Path That Led You Here -- Who the Heck Are the Joneses, and Why Are You Trying to Keep Up with Them? -- Adding to the Cart -- Emotional Buying -- Buying What You Can't Maintain -- The Influence of Advertising -- Chapter 2: Start to Become Empowered -- Crafting a Budget -- Examples of Budget Sheets -- Worksheets for Expenses -- Fixed Expenses -- Flexible Expenses -- Discretionary Expenses -- Time to Calculate -- The Frugal Philosophy -- Chapter 3: Discovering a New Outlook on Life and Money. Identify Your Values: Work, Friends, and Family The Value of Money -- The Value of Living for Tomorrow -- Chapter 4: Staying on the Right Path -- Find a Hobby -- A Life without Credit Cards -- Differentiating Needs from Wants -- Chapter 5: Teach Your Children Well -- Talk to Your Kids about Money; Kids and Values -- Prepare Your Teenagers -- Chapter 6: Introduction to Banking -- Choosing a Bank -- Credit Unions -- Types of Accounts -- What Is a Check? -- How to Open an Account -- Electronic Banking -- Types of Loans -- Investing Your Money -- Mutual Funds -- Chapter 7: Continuing on Your Financial Freedom Quest -- Find Your Green. It's Time to Step Out on Your Own Glossary -- About the Author -- Index.
Includes index.
Keywords: CONSUMER CREDIT